IDNLearn.com: Where your questions are met with thoughtful and precise answers. Get step-by-step guidance for all your technical questions from our dedicated community members.
Sagot :
To convert the equation [tex]\( y - 3x = -14 \)[/tex] to function notation [tex]\( g(x) \)[/tex], we need to solve for [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex].
Here are the steps to do so:
1. Start with the given equation:
[tex]\[ y - 3x = -14 \][/tex]
2. Solve for [tex]\( y \)[/tex] by isolating it on one side of the equation. To do this, add [tex]\( 3x \)[/tex] to both sides of the equation:
[tex]\[ y - 3x + 3x = -14 + 3x \][/tex]
Simplifying, we obtain:
[tex]\[ y = 3x - 14 \][/tex]
Now that we have [tex]\( y \)[/tex] expressed in terms of [tex]\( x \)[/tex], we can write the function notation [tex]\( g(x) \)[/tex]:
[tex]\[ g(x) = 3x - 14 \][/tex]
The correct function notation is [tex]\( g(x) = 3x - 14 \)[/tex], which corresponds to:
A. [tex]\( g(x) = 3x - 14 \)[/tex]
So, the correct answer is:
A. [tex]\( g(x) = 3x - 14 \)[/tex]
Here are the steps to do so:
1. Start with the given equation:
[tex]\[ y - 3x = -14 \][/tex]
2. Solve for [tex]\( y \)[/tex] by isolating it on one side of the equation. To do this, add [tex]\( 3x \)[/tex] to both sides of the equation:
[tex]\[ y - 3x + 3x = -14 + 3x \][/tex]
Simplifying, we obtain:
[tex]\[ y = 3x - 14 \][/tex]
Now that we have [tex]\( y \)[/tex] expressed in terms of [tex]\( x \)[/tex], we can write the function notation [tex]\( g(x) \)[/tex]:
[tex]\[ g(x) = 3x - 14 \][/tex]
The correct function notation is [tex]\( g(x) = 3x - 14 \)[/tex], which corresponds to:
A. [tex]\( g(x) = 3x - 14 \)[/tex]
So, the correct answer is:
A. [tex]\( g(x) = 3x - 14 \)[/tex]
We greatly appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. IDNLearn.com has the solutions to your questions. Thanks for stopping by, and see you next time for more reliable information.